A1.12 Endogenous SLPI released by rheumatoid synovial fibroblasts control BAFF-dependent-B cell activation in vitro and in the CIA and RA/SCID-arthritis models. (31st January 2014) - Kam, N W; Brentano, F; Kyburz, D; Gay, S; Filer, A; Buckley, C; Pitzalis, C; Bombardieri, M
Abstract : Background and Aims: Secretory leukocyte protease inhibitor (SLPI) is a serine protease inhibitor with potent anti-microbicidal/immunoregulatory activities. Rheumatoid arthritis (RA) is characterised by synovial niches of autoreactive B cells. Autocrine production of B cell survival factor BAFF by RA synovial fibroblasts (RASF) supports ongoing B cell activation within the RA synovium. We investigated whether SLPI: (1)is produced by Toll-like receptors (TLRs)-treated RASF and regulates B cell activation; (2)exerts immunoregulatory effects in the RA synovium/SCID chimeric model and in collagen induced arthritis (CIA). Methods: mRNA and protein expression of SLPI in RASF/RADF (dermal) stimulated with/without TLR2/TLR3/TLR4 ligands was assessed by QT-PCR and ELISA. RASF were treated with/without recombinant SLPI (rSLPI) to study: (1) BAFF expression; (2) AID expression and class-switching in co-culture with IgD+B cells. BAFF expression and antibody production were examined in rSLPI-treated RA/SCID mice. Severity of arthritis, anti-CII antibodies, and joint histopathology were studied in rSLPI-treated CIA mice. Results: Stimulation of RASF with TLR3-ligands led to a 15-fold induction of SLPI mRNA. SLPI protein was time-dependently released from TLR3-stimulated RASF, but not RADF. SLPI restrained the production of BAFF, AID and IgA/G/M in TLR3-treated RASF and co-cultures, respectively. SLPI reduced BAFF expression and IgG/IgM production in RA/SCID mice while severity of arthritis, cartilage damage and anti-CII-IgG2a were reduced in SLPI-treated CIA. Conclusion: RASF release high levels of SLPI constitutively and upon TLR3 stimulation. SLPI directly modulates BAFF and B cell activation in vitro/in vivo and reduces joint inflammation in CIA, highlighting a novel endogenous anti-inflammatory pathway with therapeutic potential in RA.